The Industrial Relations Counselors and the Professional Status - Chartier, Roger (Relations industrielles / Industrial Relations, 1965)
Can we really look upon the Industrial Relations Counselor as a professional? It is significant that the question is still being raised even within the new Society of Industrial Relations Counselors which, for almost two years, has enjoyed a fullfledged legal status like other older professional groups. The purpose of this working paper is not to prove at any cost that the question should be answered in the affirmative. Quite the contrary it is in no way based on any preconceived idea, but simply attempts to furnish the principal elements of an answer to our question and to provide food for thought on the criteria of the professional status insofar as they apply to the Industrial Relations Counselors.